Study of surface roughness during droplet impact on a heated stainless steel - Azra Idzkandar ABU zahar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This is a study of surface roughness during impact of water droplet impingion on a heated stainless steel. In this study, the effect of the droplet impingement on the surface were presented. The topic about the surface roughness were introduced in brief to provide basic information about the surface roughness itslf.